The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1123/jpah.2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Factors Associated With Screen Time Media Use: A Structural Study Among School-Aged Adolescents

Abstract: The main implication of our findings is to sensitize parents and stakeholders about the limitation of ST, including their own use that adolescents are likely to mimic. Alternative measures such as off-line time should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
2
21
1
1
Order By: Relevance
“…Overweight and obesity showed common associations in terms of high socioeconomic status, being a woman, residing in urban areas in adjusted models. These results are similar to those reported by Colombian data in 2005 (14), and in other countries such as France[22], Bangladesh[23] and Pakistan[24]. Possibly, the above results are due to the fact that overweight and obesity are consistent with a reduction in physical activity and an increase in the consumption of products with high caloric content and low nutritional value while watching television[25].…”
Section: Discussionsupporting
confidence: 89%
“…Overweight and obesity showed common associations in terms of high socioeconomic status, being a woman, residing in urban areas in adjusted models. These results are similar to those reported by Colombian data in 2005 (14), and in other countries such as France[22], Bangladesh[23] and Pakistan[24]. Possibly, the above results are due to the fact that overweight and obesity are consistent with a reduction in physical activity and an increase in the consumption of products with high caloric content and low nutritional value while watching television[25].…”
Section: Discussionsupporting
confidence: 89%
“…PA has also been associated with the psychological and social development of children through social interaction and integration 1. Previous studies have reported an association with spending more than 2 hours on media and physical inactivity in children 2,3. A national cross-sectional study of 8568 9-year-old Irish children affirmed that the risk of being overweight and obese was low in children with low sedentary behaviors and high PA 4.…”
mentioning
confidence: 94%
“…1 Previous studies have reported an association with spending more than 2 hours on media and physical inactivity in children. 2,3 A national cross-sectional study of 8568 9-year-old Irish children affirmed that the risk of being overweight and obese was low in children with low sedentary behaviors and high PA. 4 Another study on Asian school-age children and adolescents revealed low PA levels with limited of standardized and viable measurement tools. 5 Cooper and colleagues measured PA and sedentary time patterns in children and reported a 4.2% decrease in PA with each additional year of age.…”
mentioning
confidence: 99%
“…I nternet-enabled electronic devices occupy a central part of the lives of many people, in particular, children and young people (CYP); from the use of computers and smartphones for school work and gaming to connecting with friends through social media. 1,2 Since the introduction of the iPhone in 2007 and android in 2008, the technical functionality of screen-based devices has become more mobile and interactive, and so have their pervasiveness and use, leading to a rise in ownership of electronic devices by CYP from as young as three years of age. 3,4 The near-universal Internet usage among CYP is highlighted by recent statistics.…”
Section: Introductionmentioning
confidence: 99%